IMPLEMENTASI PENDIDIKAN KARAKTER PROFIL PELAJAR PANCASILA MELALUI BUDAYA SEKOLAH YANG DITERAPKAN DI SD ISLAM AL MADINA - Wita Ermayanti; Sumarno; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to describe the implementation of Pancasila student profile character education at Al Madina Islamic Elementary School and describe the culture that exists at Al Madina Islamic Elementary School. This research method uses qualitative research methods. Data collection techniques come from observation, interviews, and questionnaires. With the results of the analysis and discussion of the data obtained, it is clear that the implementation of the Pancasila Student Profile character education has met the very good criteria, namely achieving a score of 83.51, application of the character values of faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence. , critical reasoning, and creativity. Through school culture habits such as attending morning assembly, reading Asmaul Husna, mujahaddah, midday prayer, midday prayer in congregation, respecting other people with good manners, getting used to being independent in doing things, being creative in making things and giving constructive ideas or suggestions.